Factors affecting consumer’s continuance online purchase intention in Malaysia - Yap, M. F.; Cheng, Boon Liat * (Global Academy of Training & Research (GATR) Enterprise, 2013)
Objective – This paper attempts to explore the continuance purchase intention among Malaysian consumers on the internet, through the conceptual framework as modified from the Technology Acceptance Model. Methodology/Technique – The research data has been collected through the use of an internet-based survey method, with a convenience sample of 300 Malaysian respondents in June 2014; whereas, data analysis is further conducted using the SPSS software, through the measurements of a simple linear regression test, mediation test and moderation test. Findings – Results show a positive relationship between perceived usefulness and trust; while the continuance intention for online purchase is positively significant to perceived usefulness. The partial mediating role of subjective norm is further identified, between perceived usefulness and continuance intention. It is also understood that both male and female perceive the usefulness of website as an important factor toward their intention to online re-purchase. Novelty – Most of the researches are conducted solely upon the factors or purchase intention, limited studies have been done to investigate the continuance purchase intention among fellow consumers.